1990
DOI: 10.1093/clinchem/36.7.1350
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the concentrations of ferritin in serum in a healthy Australian population

Abstract: We measured by different techniques the ferritin concentration in serum in two large asymptomatic Australian population samples: 1367 bank employees and 601 insurance corporation employees. Ethanol intake, diet, the frequency of blood donation, smoking and exercise habits, and past medical history were documented. The median concentration of ferritin in serum varied according to age and sex, but was generally higher than in previously reported populations under age 65 years. Results for the two population samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(65 citation statements)
references
References 13 publications
3
60
0
2
Order By: Relevance
“…As observed in the general population, age-related changes in the iron status were also found in our HD patients (6). TSAT is known to be a useful marker to evaluate iron status, in addition to the serum iron level.…”
Section: Discussionsupporting
confidence: 85%
“…As observed in the general population, age-related changes in the iron status were also found in our HD patients (6). TSAT is known to be a useful marker to evaluate iron status, in addition to the serum iron level.…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed that significant iron overload (documented by liver biopsy) was present in 1 in 200 healthy asymptomatic Australians of European descent, which would indicate a gene frequency of 10%. 64,65 Interestingly, these results were very close to the frequencies published from various countries subsequent to the cloning of the HFE gene. 66 Graham Cooksley later extended the group's research repertoire to include the immunology of liver disease and then viral hepatitis.…”
Section: Back In Australiasupporting
confidence: 82%
“…although this is contradictory [15]. Leggett et al [12] found that heavy ethanol intake was associated with increased serum ferritin values, even amongst males without evidence of liver disease. We also found that serum ferritin decreased during abstinence: this has also been reported in other studies [ 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In alcoholics with significant liver disease, serum ferritin levels are of little value in assessing iron stores [1.1]. A recent report from Australia [12] concluded that the most important factors influencing the concentration of serum ferritin in healthy subjects were alcohol intake in men and diet in women. The aim of the present study was to compare serum ferritin concentration and transferrin saturation in patients with alcoholic and liver malignancy of unknown origin (rt = 6 ) .…”
Section: Introductionmentioning
confidence: 99%